Effects of Individual Nurse and Hospital Characteristics on Patient Adverse Events and Quality of Care: A Multilevel Analysis. Issue 4 (14th June 2018) - Lee, Seung Eun; Vincent, Catherine; Dahinten, V. Susan; Scott, Linda D.; Park, Chang Gi; Dunn Lopez, Karen
Abstract: Purpose: This study aimed to investigate effects of individual nurse and hospital characteristics on patient adverse events and quality of care using a multilevel approach. Design: This is a secondary analysis of a combination of nurse survey data ( N = 1, 053 nurses) and facility data ( N = 63 hospitals) in Canada. Methods: Multilevel ordinal logistic regression was employed to examine effects of individual nurse and hospital characteristics on patient adverse events. Multilevel linear regressions were used to investigate effects of individual nurse and hospital characteristics on quality of care. Findings: Organizational safety culture was associated with patient adverse events and quality of care. Controlling for effects of nurse and hospital characteristics, nurses in hospitals with a stronger safety culture were 64% less likely to report administration of wrong medication, time, or dose; 58% less likely to report patient falls with injury; and 60% less likely to report urinary tract infections; and were more likely to report higher levels of quality of care. Additionally, the effects of individual‐level baccalaureate education and years of experience on quality of care differed across hospitals, and hospital‐level nurse education interacted with individual‐level baccalaureate education. Conclusions: This study makes significant contributions to existing knowledge regarding the positive effect of organizational safety culture on patient adverse events and quality of care. Clinical Relevance: Healthcare organizations should strive to improve their safety culture by creating environments where healthcare providers trust each other, work collaboratively, and share accountability for patient safety and care quality.